Departures from Cost-Effectiveness Recommendations: The Impact of Health System Constraints on Priority Setting. Issue 1 (2nd January 2016) - Hauck, Katharina; Thomas, Ranjeeta; Smith, Peter C.
Abstract : Abstract —The methods and application of cost-effectiveness analysis have reached an advanced stage of development. Many decision makers consider cost-effectiveness analysis (CEA) to be a valid and feasible approach toward setting health priorities, and it has been extensively applied in evaluating interventions and developing evidence-based clinical guidelines. However, the recommendations arising from cost-effectiveness analysis are often not implemented as intended. A fundamental reason for the failure to implement is that CEA assumes a single constraint, in the form of the budget constraint, whereas in reality decision makers may be faced with numerous other constraints. The objective of this article is to develop a typology of constraints that may act as barriers to implementation of cost-effectiveness recommendations. Six categories of constraints are considered: the design of the health system; costs of implementing change; system interactions between interventions; uncertainty in estimates of costs and benefits; weak governance; and political constraints. Where possible—and if applicable—for each class of constraint, the article discusses ways in which these constraints can be taken into account by a decision maker wishing to pursue the principles of cost-effectiveness.